Pengaruh Perencanaan Pajak, Beban Pajak Tangguhan dan Beban Pajak Kini Terhadap Manajemen Laba - Bella Fitryani; Emmiliana Hartanti (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study discusess to evaluation the effect of tax planning, deferred tax expense and current tax burden on earnings management. This research was conducted at the Indonesia Stock Exchange (IDX) using annual report sampling techniques using secondary data. Secondary data analysis was performed by multiple regression using the e-views application 9. The population of this study was 13 companies listed on the Indonesia Stock Exchange (BEI) finance sector. The results of this study indicate that tax planning and deferred tax expense do not affect earnings management and tax burden now affect earnings management. As for tax planning, deferred tax expense and current tax burden which together affect earnings management.